The Role of Profitability in Mediating the Effect of Leverage on Firm Value at PT Indofarma Tbk - Ahmad Faishal Huffazd; Hafiz Dwi Prastian; Maiyaliza Maiyaliza (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to investigate how much profitability can mediate the connection between firm value and leverage at PT Indofarma Tbk between 2019 and 2023. The route analysis method was utilized in this study's quantitative methodology, and SPSS version 22 software was used for data processing. The annual study's companies' financial statements period served as the data source. With a coefficient value of -3.251 and a significance level of p = 0.000, the findings of the analysis show that leverage significantly reduces firm value; however, no real impact of leverage on profitability was found (coefficient = 0.000; p = 0.904). On the other hand, the findings demonstrates that profitability raises the worth of the company, but this relationship is not statistically significant (coefficient = 19.125; p = 0.288). These results indicate that how leverage and corporate value are related is not significantly mediated by profitability. In terms of theory, this study confirms that capital structure, especially in the form of leverage, has a direct impact on firm value without involving profitability as an intermediary channel. The practical implication of this result is the importance of controlling the debt structure so as not to cause a decrease in firm value, as well as the need for management to remain focused on improving the efficiency of asset performance. This study expands academic understanding of the dynamics between leverage, profitability, and firm value, and provides strategic insights for decision makers, especially in terms of optimal capital structure management.